Fundamental Analysis of the Perturbation Rejection Characteristics of Single-Input-Multiple-Output Systems Subject to Multiple Perturbations - Amézquita Brooks, Luis Antonio; Licéaga Castro, Jesús Ulises; Licéaga Castro, Eduardo; Martínez Vázquez, Daniel Librado; García Salazar, Octavio (2017)
Single-Input-Multiple-Output(SIMO)systemsarefoundinseveralapplications.Someofthemainconcernsare(1)thepossibility ofstabilizingalltheoutputsand(2)thepossibilityofattainingindependenttrackingcontrolofalltheoutputs.Whereasthefirst issuecanbeeasilybeelucidated,thesecondhasproventobeimpossibleinallbutafewsystems.Inmanycasesonepracticaloption istousetheinputtodriveamainoutput,takingcarethatthebehavioroftheremainingsecondaryoutputsisacceptable.Inthis configuration,inadditiontothefeaturesofthemaincontrolloop,theperturbationrejectionpropertiesofthesecondaryoutputs become important. This article analyzes the structural properties, stability, and perturbation rejection characteristics of SIMO systems. The article presents fundamental conclusions regarding the relationship of the main control loop and the perturbation rejectioncharacteristicsofthesecondaryoutputs.Asimpleandintuitiveexampleisusedtoshowhowthetheoreticalfindingscan be used to improve the design of the main control loop through its frequency domain characteristics. The results are developed usingsimplefrequencydomaintheoreticalelements,makingthefindingsrelevantforbothengineeringapplicationsandderiving furthertheoreticaldevelopments.